Examining graphic organizer for meaningful reading of EFL learners - Ayiz, Abdul; Hidayatulloh, Aris (CV. Yudhistt Fateeh, 2024)
This study applied experimental research with a quantitative approach to investigate the effectiveness of graphic organizer (GO) to enhance reading comprehension of EFL learners with good and poor reading habits. The study involved EFL learners from Duta Bangsa University in Indonesia. The samples were taken from two classes, the first was control group and the second was experimental group. Data collection in this study was conducted by using tests (including pre-tests and post-tests). The analysis of statistics was aimed to determine the mean, frequency, total score, standard deviation, and percentage. The pre-test values for the experimental group with good reading habits and poor reading habits were 55.17 and 43.41 respectively, while the post-test values for the experimental group with good reading habit were 79.88 and 61.23 for the poor reading habit. The average scores revealed that the experimental group, taught by using the GO strategy, outperformed the control group which received conventional way. Thus, it could be concluded that the GOs strategy significantly improved students' reading comprehension. This was evidenced by the experimental group's average score of 75.64 compared to the control group's average score of 62.44. The mean value of the experimental group was higher than that of the control group, and the t-test value was 4.241, with a 2-tailed significance of 0.001. This suggests that the GO strategy can be effectively integrated into teaching reading instruction of EFL learners to accelerate their reading comprehension.